Cefepime for prophylaxis of infections in the surgery of cholelithiasis. Results of a multicentric comparative trial - Del Rio, P.; Vellone, M.; Fragapane, et al., P. (Acta Biomedica Atenei Parmensis, 2008)
A multicenter, open labelled, randomized study was carried out to compare the prophylactic efficacy of Cefepime and Ceftriaxone in patients undergoing biliary tract surgery. Two hundred and nine patients were included in the study and randomized to receive preoperative infusion of 2 g Cefepime (n=107) or 2 g Ceftriaxone (n=102) both in a single i.v. administration. Antimicrobial prophylaxis was successful in preventing infections in 98.9% of patients in the Cefepime group and 97.7% in the Ceftriaxone group (p=0.3871). Both regimens were well tolerated without any adverse drug-related reactions. A single dose of Cefepime seems to be a very useful alternative to other regimens for antibiotic prophylaxis of postoperative infectious complications in the elective surgical treatment of cholelithiasis.